2021
DOI: 10.1097/bpb.0000000000000924
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment options for congenital pseudarthrosis of tibia in children: cross-union versus other options: a systematic review

Abstract: The systematic review aimed to provide a comprehensive update on various surgical treatment options for congenital pseudarthrosis of tibia (CPT) in children and the outcome achieved in terms of union, union time and complications of non-union and refracture. A literature search was performed in PubMed (including Medline) database for broad keywords: 'Congenital pseudarthrosis of tibia and children'. Studies selected included full-text articles on surgical treatments of CPT following: intra-medullary rod (IMR)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
(209 reference statements)
1
5
0
1
Order By: Relevance
“…In addition, significant LLD was observed in only one case in our study, which is similar to the result of Laine et al, and contrary to the results observed with other treatment methods. 1,28 This supports the interpretation of Laine et al 5 who contend that LLD is not an inherent risk of CPT but may be iatrogenic or secondary. All these results strengthen our confidence to manage CPT treatment by preventing fracture, decreasing tibial malalignment, improving radiographic appearance of bone quality, and preserving leg length.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, significant LLD was observed in only one case in our study, which is similar to the result of Laine et al, and contrary to the results observed with other treatment methods. 1,28 This supports the interpretation of Laine et al 5 who contend that LLD is not an inherent risk of CPT but may be iatrogenic or secondary. All these results strengthen our confidence to manage CPT treatment by preventing fracture, decreasing tibial malalignment, improving radiographic appearance of bone quality, and preserving leg length.…”
Section: Discussionsupporting
confidence: 72%
“…In terms of patient outcomes, a published systematic review concluded that the mean primary union rate in series using IMR was 67.7% and there was high non-union (17%) and refracture rate (48.1%). 28 The Ilizarov external fixator, which was proposed in the early 1970s, is capable of producing rigid and controlled fixation for compression, distraction, bone transport to the resection defect, lengthening, deformity correction, and union. 29 The overall union rate for the Ilizarov method in literature ranges from 60%–100%.…”
Section: Discussionmentioning
confidence: 99%
“…Treating nonunions due to segmental bone loss in the radius and ulna is challenging. Although techniques such as bone transport with Ilizarov exist, this technique does not work in avascular bone after infection [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the bone healing rate of 8 cases was 100% without a refracture, with an average follow-up of 7.4 years. Moreover, in a very recent meta-analysis of various surgical methods for the treatment of CPT, the results showed that cross-union achieved the best clinical results in both union rate (100%) and re-fracture rate (22.5%), which may be related to the increase of bone contact cross-sectional area [32]. Although the sample size of these reports was not very large, the results of 100% bone union were encouraging, which showed the importance of cross-union for CPT treatment.…”
Section: Discussionmentioning
confidence: 99%